2018
DOI: 10.1016/j.molmet.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte toll-like receptor 4 deficiency protects against alcohol-induced fatty liver disease

Abstract: ObjectiveRecent studies have suggested a critical role for toll-like receptor 4 (TLR4) in the development of alcoholic liver disease. As TLR4 is widely expressed throughout the body, it is unclear which TLR4-expressing cell types contribute to alcohol-induced liver damage.MethodsWe selectively ablated TLR4 in hepatocytes and myeloid cells. Male mice were fed a liquid diet containing either 5% alcohol or pair-fed a control diet for 4 weeks to examine chronic alcohol intake-induced liver damage and inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 52 publications
0
29
0
1
Order By: Relevance
“…We should not be surprised by the wide array of effects reported. This range of phenotypes seen under different conditions is characteristic of what has been observed for many factors involved in inflammatory responses, where beneficial and detrimental effects are in a tug of war, and the net effects differ between acute and chronically challenged states (197)(198)(199).…”
Section: Lipocalinmentioning
confidence: 69%
“…We should not be surprised by the wide array of effects reported. This range of phenotypes seen under different conditions is characteristic of what has been observed for many factors involved in inflammatory responses, where beneficial and detrimental effects are in a tug of war, and the net effects differ between acute and chronically challenged states (197)(198)(199).…”
Section: Lipocalinmentioning
confidence: 69%
“…Previous studies demonstrated that LPS could be responsible for the development of ethanol-induced hepatic lesions. Kupffer cell activation by endotoxin via Toll-like receptor 4 (TLR4) and its coreceptors, CD14 and MD2, causing the rapid activation of the transcription factor nuclear factor κB (NF-κB) and then leading to enhance expression of several proinflammatory cytokines, such as tumor necrosis factor α (TNF-α), interleukin (IL)-6 and interleukin (IL)-1 [ 14 , 15 , 16 , 17 ]. Indeed, these results suggest that inhibition of these mediators like LPS and NF-κB reduced production of proinflammatory molecules and delayed the pathogenesis of alcoholic liver injury [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the involvement of gut-derived endotoxin in the development of fructose-induced NAFLD ( 33 ). A similar study revealed that hepatic specific TLR4 deletion protected mice from fatty liver induced by 5% alcohol diet via decreasing the expression of hepatic inflammatory cytokines and endogenous lipogenesis ( 34 ). Saturated fatty acids (SFA) such as palmitate can activate proinflammatory signals through TLR4, inducing IL-1β and TNF-α production, as well as enhancing ROS production in hepatic infiltrating macrophages ( 35 ).…”
Section: Gut Microbiota and Liver Pathophysiologymentioning
confidence: 96%